Hubungan Antara Faktor Sosiodemografi Ibu (Pendidikan, Pekerjaan, Dan Pendapatan) Terhadap Perilaku Pemberian Asi Eksklusif Di Wilayah Kerja Puskesmas Mataram - Darmaiswara, Bagus Komang Rama Dita; Benvenuto, Ananta Fittonia; Anulus, Ayu; Wiradharma, I Gusti Agung Gede Agung (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The exclusive breastfeeding rate in Indonesia has not yet reached the national target of 80%. The low prevalence of exclusive breastfeeding poses risks to the growth, development, and immune system of infants. Maternal sociodemographic factors, such as education, occupation, and income, are believed to influence exclusive breastfeeding practices. This study aims to examine the association between maternal sociodemographic factors (education, occupation, and income) and exclusive breastfeeding practices in the working area of Mataram community health center.  This study employed a quantitative cross-sectional design. Sampling was conducted using the cluster sampling technique, with 95 participants selected based on inclusion and exclusion criteria. The independent variables are education, employment, and income, while the dependent variable is exclusive breastfeeding. Data analysis was performed using the Chi-Square test. Significant correlation were observed between education (PR = 1.88; 95% CI = 1.23–2.86; p = 0.009), income (PR = 1.80; 95% CI = 1.16–2.78; p = 0.015), and occupation (PR = 0.53; 95% CI = 0.34–0.81; p = 0.009) with exclusive breastfeeding practices. Maternal education, income, and occupational status influence exclusive breastfeeding practices. Mothers with higher educational attainment and income levels are more likely to engage in exclusive breastfeeding, whereas working mothers are less likely to do so.   Keywords: Exclusive Breastfeeding, Occupation, Education, Income, Maternal Sociodemographic  ABSTRAK Pemberian ASI eksklusif di Indonesia belum mencapai target nasional yaitu sebesar 80%. Rendahnya pemberian ASI eksklusif ini menimbulkan risiko terhadap tumbuh kembang dan kekebalan tubuh bayi. Faktor-faktor sosiodemografi ibu seperti pendidikan, pekerjaan, dan pendapatan ibu diyakini mempengaruhi perilaku pemberian ASI eksklusif. Penelitian ini bertujuan untuk mengetahui hubungan antara faktor sosiodemografi ibu (pendidikan, pekerjaan, dan pendapatan) terhadap perilaku pemberian ASI eksklusif di wilayah kerja Puskesmas Mataram. Penelitian ini adalah penelitian kuantitatif dengan desain cross-sectional. Pengambilan sampel menggunakan teknik cluster sampling. Sebanyak 95 sampel dipilih yang telah memenuhi kriteria inklusi dan eksklusi. Variabel independen adalah pendidikan, pekerjaan, dan pendapatan. Variabel dependen adalah ASI eksklusif. Analisis data dilakukan dengan uji Chi-Square. Terdapat hubungan pendidikan (PR = 1,88; 95% CI = 1,23-2,86; p = 0,009), pendapatan (PR = 1,80; 95% CI = 1,16-2,78; p = 0,015), dan pekerjaan (PR = 0,53; 95% CI = 0,34-0,81; p = 0,009) dengan perilaku pemberian ASI eksklusif. Pendidikan, pendapatan, dan status pekerjaan ibu memengaruhi perilaku pemberian ASI eksklusif, dengan ibu berpendidikan lebih tinggi dan berpendapatan lebih besar cenderung lebih sering memberikan ASI eksklusif sementara ibu yang bekerja cenderung memiliki peluang lebih rendah untuk melakukannya. Kata Kunci:  ASI Eksklusif, Pekerjaan, Pendidikan, Pendapatan, Sosiodemografi